Beyond superlatives : regenerating Whitehead's philosophy of experience - Faber, Roland, 1960-; Hustwit, J. R.; Phelps, Hollis (Cambridge Scholars Publishing, 2014)
This collection of essays, drawn from the latest generation of Whitehead scholars, explores how, in the deconstruction of certain concepts, an unceasing invitation of possibility and change is released, both in relation to ongoing philosophical conversations, and as applied to lived experience. The essays make a significant intervention in the field of Whiteheadian scholarship by creating new intersections and paths that extend Whitehead's thought in novel, and often unexpected, directions. ...